Groundwater quality assessment of the BDP aquifer in rural area of India - Pinaki Ghosh; Debashis Chatterjee; Samir Kumar Mukherjee (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Groundwater is gradually more used worldwide for domestic, industrial and agricultural production. The presence of natural Arsenic (As) release of ground water is a global issues and notably more severe in south East Asia particularly India and Bangladesh. The high occurrence of As in ground water in India and Bangladesh is a challenging public health issue because As is one of the carcinogen metalloid. A full scale ground level study will be required to find out the precise role of these local land-use patterns. In the present work few As affected village of Nadia district has been studied. The most significant matter specially derived fresh organic matter is an important issue to release As to ground water. Finally the study suggests that Fe reduction link with microbial mobilization of As is important process.